CORRELATION BETWEEN CONJUGATION LENGTH AND NONRADIATIVE RELAXATION RATE IN POLY(PARA-PHENYLENE VINYLENE) - A PICOSECOND PHOTOLUMINESCENCE STUDY - Wong, K; Bradley, D; Hayes, W; Ryan, J; Friend, R; Lindenberger, H; Roth, S (1987)
Time-resolved photoluminescence of poly(p-phenylene vinylene) in the picosecond regime shows that the non-radiative decay rate increases with increasing polymer chain conjugation length and that the luminescence decay is much faster for excitation parallel to the polymer chain than for perpendicular excitation. The results provide evidence for bimolecular recombination processes.